2023
DOI: 10.3389/fgene.2023.1158029
|View full text |Cite
|
Sign up to set email alerts
|

Identification of featured necroptosis-related genes and imbalanced immune infiltration in sepsis via machine learning

Abstract: Background: The precise diagnostic and prognostic biological markers were needed in immunotherapy for sepsis. Considering the role of necroptosis and immune cell infiltration in sepsis, differentially expressed necroptosis-related genes (DE-NRGs) were identified, and the relationship between DE-NRGs and the immune microenvironment in sepsis was analyzed.Methods: Machine learning algorithms were applied for screening hub genes related to necroptosis in the training cohort. CIBERSORT algorithms were employed for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
(39 reference statements)
1
5
0
Order By: Relevance
“…Previous studies have revealed that the down-regulation of LEF1, BACH2, and BCL2 have good prognostic value in sepsis through bioinformatics analysis based on machine algorithms [42], as we found in the public data. LEF1 can be used as a biomarker in hematologic tumors, oral cancer, and colorectal cancer.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Previous studies have revealed that the down-regulation of LEF1, BACH2, and BCL2 have good prognostic value in sepsis through bioinformatics analysis based on machine algorithms [42], as we found in the public data. LEF1 can be used as a biomarker in hematologic tumors, oral cancer, and colorectal cancer.…”
Section: Discussionsupporting
confidence: 70%
“…Myocardial dysfunction and liver injury are common organ injuries in sepsis, and they are closely related to necroptosis, so it is vital to nd the key genes of sepsis, especially those related to necroptosis. She et al have preliminarily explored that the potential necroptosis-biomarkers with good prognostic value in sepsis using several machine learning algorithms [42]. This study was conducted to further explore the underlying functions and regulatory networks targeting biomarkers as well as the functionality correlations of which with key necroptotic signaling pathway molecules, such as RIPK1, RIPK3 and MLKL.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers reported that necroptosis pathway (another form of PCD) was significantly activated in sepsis ( Shashaty et al, 2019 ; Reilly et al, 2022 ). Han She et al ( She et al, 2023 ) identified BCL2 as one of the necroptosis-related hub genes in sepsis, highlighting its diagnostic and prognostic value. Moreover, necroptosis and pyroptosis (another form of PCD) pathways collaborated to aggravate tissue injury in the process of sepsis ( Chen et al, 2020 ), and BCL2 constrained the induction of these two pathways through interaction with a BCL2-homology-3 like domain ( Shi and Kehrl, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the diagnostic value of STAT3 in sepsis-induced myocardial disease and sepsis-related respiratory distress syndrome ( Zhang et al, 2019 ; Song et al, 2023 ). Metabolism-related genes ( She et al, 2022 ), necrosis-related genes ( She et al, 2023 ), immune-related genes ( Zheng et al, 2022 ) common DEGs related to sepsis and metabolic syndrome ( Tao et al, 2023 ), apoptosis-related genes ( Wang et al, 2022 ), inflammation response signature genes ( Jiang et al, 2022 ), and signature genes for septic shock in children ( Fan et al, 2022 ) have all shown some efficacy in the diagnosis and prognostic assessment of sepsis. In addition, metabolites based on metabolomics analysis ( Li Y. et al, 2023 ), m6A regulatory factors ( Li F. et al, 2023 ), and non-coding RNAs such as miR-147b ( Trung et al, 2021 ), lncRNA THAP9-AS1 , and TSPOAP1-AS1 ( Wu et al, 2020 ) have all been reported as potential diagnostic or prognostic indicators for sepsis or septic shock.…”
Section: Discussionmentioning
confidence: 99%